The Reinvention of Mexico in Contemporary Spanish Travel Writing - Hanley, Jane, 1981- (Book collections on Project MUSE., 2021)
"The impact of the history of transatlantic movement in the Spanish-speaking world on present-day concepts of Mexico and Latin America"--